Magnetic composite biomaterials for tissue engineering - Gil, Sara (2014)
Magnetic nanoparticles (MNPs) have been increasingly used in tissue engineering and regenerative medicine. These particles have been mainly employed as elements directly incorporated into cells or interacting with cell membranes; however, MNPs are now being combined with biomaterials to create other functionalities of the structural framework used to support cells, namely for controlling cellular responses and for enhancing drug delivery and release. This mini-review summarizes and highlights the latest developments and applications of polymeric/ceramic biomimetic scaffolds and hydrogels that contain MNPs for such purposes, also addressing future perspectives for the use of these magnetic composite biomaterials in biomedicine.